2023
DOI: 10.3390/ph16081108
|View full text |Cite
|
Sign up to set email alerts
|

Mannose-Functionalized Isoniazid-Loaded Nanostructured Lipid Carriers for Pulmonary Delivery: In Vitro Prospects and In Vivo Therapeutic Efficacy Assessment

Abstract: Resistance to isoniazid (INH) is common and increases the possibility of acquiring multidrug-resistant tuberculosis. For this study, isoniazid-loaded nanostructured lipid carriers (INH-NLCs) were developed and effectively functionalized with mannose (Man) to enhance the residence time of the drug within the lungs via specific delivery and increase the therapeutic efficacy of the formulation. The mannose-functionalized isoniazid-loaded nanostructured lipid carrier (Man-INH-NLC) formulation was evaluated with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In this study, 5 mg of completely dried metal NPs and 2 mL of plant aqueous extract were mixed with KBr, dried, and compressed to form KBr pellets and further spectra were obtained. Dynamic light scattering (DLS) and Zeta potential by Zetasizer nano series -Nano ZS 90 (Malvern Panalytical) was used to study the size distribution of the synthesized NPs in the colloidal solution [33]. The prepared NPs were dispersed in Milli-Q water with ultrasonification so that no extra peak appeared.…”
Section: Characterizationmentioning
confidence: 99%
“…In this study, 5 mg of completely dried metal NPs and 2 mL of plant aqueous extract were mixed with KBr, dried, and compressed to form KBr pellets and further spectra were obtained. Dynamic light scattering (DLS) and Zeta potential by Zetasizer nano series -Nano ZS 90 (Malvern Panalytical) was used to study the size distribution of the synthesized NPs in the colloidal solution [33]. The prepared NPs were dispersed in Milli-Q water with ultrasonification so that no extra peak appeared.…”
Section: Characterizationmentioning
confidence: 99%
“…The model that created a linear plot and had the highest (r 2 ) value was the best fit for the drug release data [28].…”
Section: Kinetic Studymentioning
confidence: 99%
“…Based on these results, targeting the mannose receptor for TB treatment appears promising, and intracellular co-localization of the bacteria and the nanocarrier is more likely given that they may use the same macrophage entry channel [135]. Numerous studies have concentrated on macrophage targeting via the mannose receptor and shown enhanced absorption of the mannosylated nanocarriers compared to non-targeted formulations [157,158].…”
Section: Mannose Targetingmentioning
confidence: 99%